EVALUASI KOMPETENSI PROFESIONALISME GURU MATA PELAJARAN GEOGRAFI DAN IPS DI SMP N 1 KARIMUNJAWA, MTs DAN MA NU SAFINATUL HUDA PULAU KARIMUNJAWA - Benardi, Andi Irwan (Universitas Pendidikan Ganesha, 2018)
AbstractResearch on the evaluation of teacher professionalism competence on geography and ips subjects in smp n 1 karimunjawa, mts safinatul huda karimunjawa and ma nu safinatul huda karimunjawa aims to know the level of professionalism of geography teacher and ips at karimunjawa island schools especially in smp n 1 karimunjawa, mts safinatul huda karimunjawa and ma nu safinatul huda karimunjawa and constraints faced by geography teachers and ips in building professional competence. The competency indicators used for this research are pedagogical, professional, personality and social competence. The result of professional competence of teacher of geography and ips in karimunjawa categorized as competent. Constraints faced by teachers to improve professional competence include lack of school infrastructure and media used for classroom learning. Suggestion in this research is that school is expected to improve facility to support teacher performance so as to achieve professional competence of geography teacher and ips to be better. Teachers are expected to be able to develop their performance and meet teacher standards by increasing knowledge insight in the field that is experienced through teacher education training.